Somatic and mental health of obese children - T.V. Sorokman; O.V. Makarova (Miz︠h︡narodnyĭ endokrynolohichnyĭ z︠h︡urnal, 2020)
Background. Obesity belongs to the group of psychosomatic diseases. Already in childhood with excess body weight, the functional abnormalities of the central and autonomic nervous systems, endocrine glands, internal organs are determined. The purpose was to investigate somatic and mental health status in overweight and obese children. Materials and methods. Three hundred and twenty-five children aged 13–18 years old were studied (overweight (OW) — 75; obesity (Ob) — 45, underweight — 30, normal body weight — 175). Body mass index was estimated using standardized percentile tables (WHO, 2007). All children were evaluated by H. Eysenck Personal Questionnaire, M. Luscher color test, S. Rosenzweig drawing association test modified by S. Lukin, A. Suvorov. The statistical modules of Statistica v.6.0 using correlation analysis were used for statistical processing of the results (quantitative and qualitative analysis with calculation of average and relative values, determination of statistical significance by the criterion χ2 for absolute values and by Fisher angular transformation method pφ for relative values). Results. More than half of children with OW and Ob have somatic health disorders: goiter I–II (46.6 %), functional (30.8 %), and structural (22.8 %) gallbladder disorders, diffuse pancreatic changes (100 %), gastroduodenitis (38.4 %), gastritis (34.1 %), reflux esophagitis (18.8 %), in every third teenager (33.3 %) experienced insufficiency of the lower cardiac sphincter. Half of the children with Ob had an intrapsychological orientation, anxious and egocentric type of reactions, asthenodepressive accentuation of character. The expressiveness of personal maladaptation of children with OW and Ob increased with the disease progression (OR 5.63, 95% CI 2.11–15.08). One child in three with Ob had multiple fears and phobias. Among the psychological types of personality, introversion (71.1 %) significantly dominated over extraversion (8.8 %) and ambiversion (19.1 %). Conclusions. The results obtained determine the need to monitor the risk factors for the development of obesity, the health status of overweight and obese children, and provide medical and psychological support to maintain health and improve quality of life.